1986
DOI: 10.1016/0266-7681(86)90018-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary flexor tendon repair: The mechanical limitations of the modified kessler technique

Abstract: The aim of primary suture of flexor tendons in the hand is to achieve full function as soon as possible with a one stage operation. Much interest has been aroused by this subject and more recently by the possibility of improving results by postoperative active movement of the repaired tendon. We report the results of mechanical testing of the modified Kessler suture which suggests that the peripheral stitch is an important structural component of the suture. It is not merely a 'tucking in' stitch, but is essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(43 citation statements)
references
References 12 publications
4
39
0
Order By: Relevance
“…Mashadi and Amis, 31 however, showed that placement of the peripheral suture within the substance of the tendon was 83% stronger than that placed in the epitenon fibers only. Wade et al, 32 using a 2-strand Kessler grasping repair with and without a simple running peripheral suture, showed that the use of a peripheral suture can improve the early gap formation properties dramatically. Kubota et al, 5 using a 4-strand core repair with and without a cross-stitch peripheral suture, 29 noted that the peripheral suture can provide 80% and 36% of the total initial gap forming strength and load to failure, respectively.…”
Section: Figurementioning
confidence: 98%
“…Mashadi and Amis, 31 however, showed that placement of the peripheral suture within the substance of the tendon was 83% stronger than that placed in the epitenon fibers only. Wade et al, 32 using a 2-strand Kessler grasping repair with and without a simple running peripheral suture, showed that the use of a peripheral suture can improve the early gap formation properties dramatically. Kubota et al, 5 using a 4-strand core repair with and without a cross-stitch peripheral suture, 29 noted that the peripheral suture can provide 80% and 36% of the total initial gap forming strength and load to failure, respectively.…”
Section: Figurementioning
confidence: 98%
“…Originally, the circumferential or epitendinous suture was conceived of to "tidy up" the repair site; 35 however, these circumferential sutures have been found to improve resistance to gap formation and provide as much as 50% of the strength to the ultimate load to failure. [37][38][39][40] A 1984 survey of 378 members of the American Society for Surgery of the Hand found that almost 97% of respondents use some form of a running circumferential suture to complete their primary flexor tendon repairs. 36 The IHM circumferential suture has demonstrated superior 2-mm gap force and ultimate load to failure when compared with a simple running or a cross-locked circumferential suture.…”
mentioning
confidence: 99%
“…It is associated with the formation of restrictive adhesions between the tendon repair and its surrounding synovial sheath and with a poor overall outcome [15,16]. The tensile strength at failure of modified Kessler tendon repairs performed using various suture materials and tested under laboratory conditions [15][16][17][18][19] ranges between 21 N [19] and 47 N [15]. Thus even the strongest thermal bonds in our study were not strong enough to replace sutured repairs completely.…”
Section: Could Thermal Bonds Be Strong Enough For Use In Clinical Tenmentioning
confidence: 82%
“…Thus even the strongest thermal bonds in our study were not strong enough to replace sutured repairs completely. However, in a number of cases thermal bonds were of equal or greater strength than the load at which gaping occurred in these studies (range 15 N [17] to 25 N [18]) and at which epitendinous sutures alone gaped or failed (range 9-17 N [20]). Thus the only role if any for thermal bonding in tendon repair would appear to be as a replacement for, or a way of augmenting the strength of epitendinous sutures.…”
Section: Could Thermal Bonds Be Strong Enough For Use In Clinical Tenmentioning
confidence: 99%